Novel Therapeutic Targets and Immune Dysfunction in Malignant Pleural Mesothelioma - Lapidot, Moshe; Saladi, Srinivas Vinod; Salgia, Ravi; Sattler, Martin (Frontiers in Pharmacology, 2022)
Advances in the treatment of malignant pleural mesothelioma (MPM) have been disappointing, despite the apparent need for new therapeutic options for this rare and devastating cancer. Drug resistance is common and surgical intervention has brought benefits only to a subset of patients. MPM is a heterogenous disease with a surprisingly low mutation rate and recent sequencing efforts have confirmed alterations in a limited number of tumor suppressors that do not provide apparent insights into the molecular mechanisms that drive this malignancy. There is increasing evidence that epigenetic regulation leads to immune evasion and transformation in MPM. Further, the low efficacy of immune checkpoint inhibitors is consistent with a suppression of genes involved in the anti-tumor immune response. We review three promising emerging therapeutic targets (STAT3, KDM4A, heparanase) and highlight their potential effects on the immune response.